The Interference of Identical Nominal Factors in the Positions of Stopping and Starting - Al-Mufarji, Audy Saddam Ahmed Hussein; Al-Jubouri, Nafeh Alwan Bahlol Saleh (Journal of Ecohumanism, 2025)
this study explores the interference caused by identical nominal factors in the dynamic transitions between starting and stopping positions within systems or processes. Identical nominal factors, defined as elements with the same characteristics or nominal values, often lead to overlaps or ambiguities in system behaviors, causing inefficiencies, delays, or errors in operations. By analyzing case studies and theoretical models across various disciplines—such as manufacturing systems, transportation logistics, and automated control systems—this paper identifies key patterns of interference. The findings highlight the conditions under which such factors impede smooth transitions and propose strategies to mitigate their effects. This research aims to improve the reliability and performance of systems by refining design principles and operational protocols that account for these interferences.